Modell basierte Analyse von Wasserströmen im internationalen Handel von Agrarprodukten - Roland Treitler; Helmut Berrer (FIW - Research Centre International Economics, 2010)
– The amount of water embodied in Austrian imports of selected agricultural products is quantified. These imports are analysed by a dynamic model that is based on the water footprint concept. The model quantifies the water savings potential using a database including more than 200 countries and regions. Austria could save up to 28% of the water embodied in coffee by substituting the current coffee imports from water inefficient countries by efficiently produced coffee. The water savings potential from wheat imports amounts to 22% that from orange imports equals almost 20% of the current amount of embodied water. We calculate a global water value equal to 0.013 per cubic meter of water. The international trade of coffee, wheat and oranges trades embodied water equal to 51.6 billions per year with a share of 92.6% ( 47.8 billions) traded at commodity exchanges.
Keywords: Q56; Q17; Q25; 330; Water; Water Footprint; Water Value; International Trade